Iš bibliotekų istorijos Biržuose ir Biržų apylinkėse XVI–XIX a. - Vokėnaitė, Aldona (Knygotyra, 1972)
The first libraries arose in Biržai in the 16th century. They were the library of the prince’s palace and church libraries. In the years of Reformation and counter-reformation collections of books appeared in schools and at homes of private persons. Somewhat later libraries were created in manors. The abolition of serfdom created new conditions for reading and development of libraries. But the tsarist government’s interdict against the Lithuanian printing hindered the formation of libraries. Illegal means of dissemination of books emerged. According to reliable information a number of various libraries appeared and functioned in Biržai and the district during the period of 400 years. Later on many books from these libraries found themselves in the libraries accessible for the general public. During the period in question the political and economic conditions were not favourable to form really public and free to all libraries.